Relationship between in vitro susceptibility test results for chloramphenicol and production of chloramphenicol acetyltransferase by Haemophilus influenzae, Streptococcus pneumoniae, and Aerococcus species. - Matthews, H W (1988)
Haemophilus influenzae, Streptococcus pneumoniae, and Aerococcus species were tested for susceptibility to chloramphenicol by standard broth microdilution and disk-diffusion methods. MICs and zone diameter breakpoints were correlated with production of chloramphenicol acetyltransferase (CAT). A comparison of MICs and zone diameters indicated that the interpretative criteria for H. influenzae and S. pneumoniae should be an MIC of less than or equal to 4 micrograms/ml or a zone diameter greater than or equal to 25 mm for susceptible strains and an MIC of greater than or equal to 8 micrograms/ml or a zone diameter of less than or equal to 20 mm for resistant strains; for Aerococcus species, interpretative criteria should be an MIC of less than or equal to 8 micrograms/ml or a zone diameter of greater than or equal to 20 mm for susceptible strains and an MIC of greater than or equal to 32 micrograms/ml or a zone diameter of less than or equal to 12 mm for resistant strains. All but four strains of H. influenzae and one strain of S. pneumoniae that were resistant to chloramphenicol by these criteria produced CAT. For Aerococcus species, however, chloramphenicol-resistant strains were negative for CAT as determined by a commercially available disk test. When comparing susceptibility results with CAT production, thiamphenicol was a better indicator of the presence of the enzyme than chloramphenicol and may be useful in assaying resistance to chloramphenicol.